Antecedents and Consequences of Brand Image and Perceived Quality of Wardah Face Mask Prospects - Geraldine, Jeane; Ernawadi, Yadi (Jurnal Ilmu Manajemen Advantage, 2024)
The aim of this research is to examine the antecedents and consequences of brand image and perceived quality in Cimahi City. 20 respondents were prospects for Wardah face masks in this study. The cross-sectional or one shot method was used to obtain data. The instrument has passed the validity and reliability tests by including outer model measurements, namely convergent validity, discriminant validity, and composite reliability. The data analysis technique used is structural equation modeling (SEM) using the SmartPLS version 3.0 tool. Of the fourteen research hypotheses proposed, twelve were supported by empirical data. With the results of the study, quantity and credibility have a positive effect on brand image and perceived quality, then brand image and perceived quality have a positive effect on purchase intention, then brand image and perceived quality mediate the effect of quantity and credibility on purchase intention. The difference from this study is the object studied by Wardah face masks and the research locus in Cimahi City. The results of this study are expected to provide benefits for further research and the assessed Wardah or similar beauty industries related to designing strategies relevant to improving the quality of these attributes.